find

Asked by  | 24th May, 2009, 12:16: PM

Expert Answer:

t(1 + x2) = x,

rearranging, we get,

t = x/(1 + x2)

substituting this in second equation

x2 + [x/(1 + x2)]2 = y,

x2 + x2/(1 + x2)2 = y

Hence dy/dx = 2x + [(1 + x2)2. 2x  -  x2. 2(1 + x2).2x]/(1 + x2)4 

using x = 2, and evaluating gives,

dy/dx = 488/125

Regards,

Team,

TopperLearning.

 

Answered by  | 20th Aug, 2009, 10:33: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.